EKSPANSI BOLLYWOOD MELALUI TAYANGAN PADA TELEVISI DI INDONESIA - Susanti, Dwi (LENTERA, 2018)
Cultural globalization entered Indonesia through the media, such as television. Foreign culture be able to enter freely into the Indonesian market through the television. Television one of popular medium because it is combine the audio and visual. The discovery of television not only brought thet changes in technological development, but it changes to people's lives. People's lives can be influenced by television, such as influenced on education, economy, social life and even culture in society. In line with its development, television has also transformed in terms of technology and content presented to audiences. Along with the development of various programs in Indonesia, the television choose to show of programs that contained Bollywood content. Globalization of Bollywood media and culture is brought and disseminated to Indonesian people through programs on television.